2019
DOI: 10.1002/adfm.201903641
|View full text |Cite
|
Sign up to set email alerts
|

Graphitic Nanocarbon with Engineered Defects for High‐Performance Potassium‐Ion Battery Anodes

Abstract: The application of graphite anodes in potassium-ion batteries (KIB) is limited by the large variation in lattice volume and the low diffusion coefficient of potassium ions during (de)potassiation. This study demonstrates nitrogendoped, defect-rich graphitic nanocarbons (GNCs) as high-performance KIB anodes. The GNCs with controllable defect densities are synthesized by annealing an ethylenediaminetetraacetic acid nickel coordination compound. The GNCs show better performance than the previously reported thin-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
182
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 242 publications
(209 citation statements)
references
References 59 publications
3
182
2
1
Order By: Relevance
“…In the initial cycles, the anodic peak at 0.7 V shifts slightly and stabilizes due to the structural re-arrangement during (de)potassiation. [23] Compared with ENDC500, ENDC700 and NDC900 electrodes show smaller areas of the CV curves (Supporting Information, Figure S12), indicating decreased reversible capacity. The galvanostatic chargedischarge (GCD) curves (Figure 4 b) demonstrate similar behavior as the CV curves.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the initial cycles, the anodic peak at 0.7 V shifts slightly and stabilizes due to the structural re-arrangement during (de)potassiation. [23] Compared with ENDC500, ENDC700 and NDC900 electrodes show smaller areas of the CV curves (Supporting Information, Figure S12), indicating decreased reversible capacity. The galvanostatic chargedischarge (GCD) curves (Figure 4 b) demonstrate similar behavior as the CV curves.…”
Section: Resultsmentioning
confidence: 99%
“…[20][21][22] Nonetheless, the rate capability and cycling stability of graphite anode for PIB are still limited owing to the large volume variation (58 %) during (de)potassiation, the low diffusion coefficient of K-ion, and the irreversible trapping of K atoms in graphite lattices. [23][24][25][26] To compete with the LIB technology or achieve a low energy storage cost, the capacity of carbonaceous anodes of PIB should be improved to be comparable to the specific capacity of LiC 6 . For the sake of enhanced capacity of carbonaceous anodes in PIB, several parameters must be carefully controlled, including 1) the (002) lattice spacing should be made large enough for efficient (de)potassiation; [27,28] 2) the defect-induced adsorption mechanism should be engineered to enhance K-ion storage beyond the intercalation mechanism (here, defects refer to CÀC sp 3 defects, and heteroatom-doping-induced defects).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrochemical test results showed that the prepared N‐GCNs exhibited a reversible capacity and high cycling stability. In addition, by adjusting the annealing temperature, Zhang et al prepared graphitic nanocarbons with controllable defect density of doped nitrogen and CC sp 3 and graphene layer length for potassium‐ion battery anodes . On the one hand, the production of CC sp 3 defects in graphite carbon provides a way for effective diffusion of potassium ions.…”
Section: Defective Electrode Materials For Rechargeable Batteriesmentioning
confidence: 99%